2013
DOI: 10.1016/j.pmrj.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Cardiac Rehabilitation Initiation and the Effect on Survival

Abstract: In a predominantly minority population, racial disparities exist among cardiac rehabilitation participants. Minorities were less likely to initiate cardiac rehabilitation. Gender, referral patterns, and the presence of copayment did not influence initiation. Cardiac rehabilitation initiation was associated with decreased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Our study represents 1 of the largest analyses to date focused on CR participation following AMI. Prior studies have often been limited to data from single or several hospitals or a focus on the Medicare population . Similar to these studies, we found a strong association between CR nonparticipation and female sex, nonwhite race, lack of insurance, tobacco use, and lower education levels.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study represents 1 of the largest analyses to date focused on CR participation following AMI. Prior studies have often been limited to data from single or several hospitals or a focus on the Medicare population . Similar to these studies, we found a strong association between CR nonparticipation and female sex, nonwhite race, lack of insurance, tobacco use, and lower education levels.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, even when prescribed, rates of patient participation in CR have been historically low due to limited access, lack of insurance coverage, and out-of-pocket cost for co-pays. [8][9][10] Although data from the 1990s and early 2000s have demonstrated the effect of demographic and socioeconomic factors on CR referral and participation, [10][11][12][13][14][15] current data are lacking. The goal of this study was to assess the current trends in CR participation after AMI in the United States and to identify predictors of participation.…”
mentioning
confidence: 99%
“…Cardiac rehabilitation initiation was associated with cardiologist involvement. Initiation was associated with a survival benefit, and there were no differences between white and nonwhite patients in survival benefit for those patients initiating rehabilitation (74). Even in a community of a predominantly minority population, racial disparity exists among cardiac rehabilitation participants.…”
Section: Patient/health Care Provider Team-based Engagement Strategiesmentioning
confidence: 99%
“…CR participation increases quality of life and decreases the risk of all‐cause mortality, CVD mortality, and recurrent CVD events . Unfortunately, CR is profoundly underutilized, with only 15% to 20% of eligible patients participating in CR programs nationally . CR participation rates are particularly low in underrepresented minorities, and are lower than the national average in the southeastern United States …”
Section: Introductionmentioning
confidence: 99%
“…Barriers to participation in CR are myriad, spanning patient, physician, community, and health system factors, and there are marked ethnic and regional disparities in CR referral and participation rates . One of these patient factors, individual socioeconomic status, is directly associated with CR participation .…”
Section: Introductionmentioning
confidence: 99%